The Hg-Pd-Te system: phase relations involving temagamite and a new ternary phase - Drabek,M.; Vymazalova,A.; Laufek,F.; Tuhy,M. (Journal of Geosciences, 2021)
Phase relations in the Hg-Pd-Te system were studied at 350 °C using the silica glass tube method. The following binary phases were confirmed to be stable at 350 °C: PdHg (potarite), HgTe (coloradoite), Pd13Te3, Pd20Te7 (keithconnite), Pd7Te3, Pd9Te4 (telluropalladinite), Pd3Te2, PdTe (kotulskite), and PdTe2 (merenskyite). Kotulskite (PdTe) dissolves up to 8 at. % Hg at 350 °C. Other palladium tellurides do not dissolve Hg. Two ternary phases were proved to be stable in the system at 350 °C: Pd3HgTe3 (temagamite) and a new phase Pd4HgTe3. The Pd4HgTe3 phase is orthorhombic, Pnma space group with unit-cell parameters a = 13.1520(2), b = 11.6879(2), c = 4.25758(5) Å, V = 654.480(5) Å3 and Z = 4. The Pd4HgTe3 phase can be viewed as a ternary ordered variant of the Hg-bearing kotulskite. Synthetic temagamite forms stable assemblages with several phases representing minerals merenskyite and coloradoite, coloradoite and potarite, merenskyite and kotulskite, phase Pd4HgTe3 and kotulskite s.s., and phase Pd4HgTe3 and potarite. The occurrence of temagamite and its associations indicate the formation of mineralization below 570 °C. The new phase Pd4HgTe3 forms stable associations with synthetic analogs of temagamite and potarite, potarite and telluropalladinite, telluropalladinite and kotulskite s.s., temagamite and kotulskite s.s. The phase Pd4HgTe3 can be expected to be found in such associations under natural conditions.
Keywords: Hg-Pd-Te system; Pd-Hg tellurides; phase relations; temagamite; platinum-group minerals; new ternary phase